Influence of patient satisfaction through commitment to loyalty inpatient HOSPITALS Jayapura - Setyajidi, Bambang; Kambuaya, B.; Tuhumena, Ruben; Bharanti, Elita (Advances in Social Sciences Research Journal, 2018)
The study was done at the Jayapura Public Hospital Area. The number of respondents was 294 patients. Variable measurement research done using multiple indicator, then analyzed using structural equation model (Structural Equation Modeling) Software with AMOS, and SPSS. Ver. 21. The findings of this study are: Patient satisfaction is positive and significant effect against the commitment of the Patient; Patient satisfaction and positive effect not significant Loyalty towards Patients;; The patient’s commitment to a positive and significant effect against Patient Loyalty. Furthermore, satisfaction, confidence, and commitment are positioned as the mediation between the variable quality of service with loyalty. So, orisinilitas findings in these studies is variable commitment as mediation of service quality, customer satisfaction, loyalty and confidence. In General, the findings of this study provide strong support against the role of commitment required in building long term relationships and provide strong support for the mediation mechanism.